The language of statutes laws and their interpretation - Solan, Lawrence, 1952- (Chicago, Ill. ; London : University of Chicago Press, 2010)
Solan provides an introduction to statutory interpretation rejecting the arguments tht judges have either too much or two little leeway, & explaining how & why a certain number of interpretative problems are simply inevitable.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Interpretation and construction; Law; Jurisprudence & general issues; Legal systems: general